Theoretical background to the forensic characteristics formation for hostage-taking of a government official or law enforcement officer. - V. O. Husieva; O. Yu. Prokopenko (Law and Safety)
The widespread aggression of the Russian Federation against Ukraine has led to an increase in the number of people in vulnerable situations, including a significant increase in the cases of disappearances and hostage-taking. In this regard, there is a need to improve the methods of investigating the hostage-taking of government officials or law enforcement officers. When developing and formulating an appropriate investigation methodology, it is first of all necessary to determine the forensic characteristics of the relevant crime.